Kegiatan Pelatihan dan Pengabdian kepada Masyarakat dalam Pemahaman Penggunaan Tools AI untuk Membuat Konten - Christy, Christy; Jennifer Jocelyn; Jennifer Velensia Santoti; Nicholas Edison; Ricko Andreas Kartono; Hartati, Ery (Jurnal Pengabdian, 2025)
This training activity aims to improve the understanding of students of SMP Xaverius Maria Palembang regarding the use of artificial intelligence (AI) tools to create digital content, such as graphic design, video, and music. The hands-on practice-based training method is used to provide students with real experience in using AI applications, such as ChatGPT, Microsoft Designer, Luma AI, and Udio AI. The results of the training show that students not only understand the basic concepts of AI, but are also able to produce more innovative and creative content. Evaluation through interactive quizzes shows an increase in student understanding, although there are some challenges in understanding certain technical terms. This training has succeeded in encouraging students to become active and ethical digital creators, supporting their digital literacy to face the era of increasingly developing technology.